Influences of Librarians’ Service Qualities on Academic Library E-catalog Use - Mahendra Adhi Nugroho (LPPM UNY, 2011)
This study is aimed at knowing the influences of librarians’ service qualities on E-catalog use. It tries to split service quality into two main blocks, i.e. physical service quality and process service quality, and synthesizes service quality constructs in four different constructs based on SERQUAL constructs. A total of 220 valid samples from four universities with almost similar academic library E-catalogue systems were used for testing 5 hypotheses by means of the Smart PLS 2.0 software. The results show that reliability, responsiveness, assurance, and empathy positively influence librarians’ service qualities. However, librarian service quality does not significantly influence E-catalog use.